Molecular epidemiology of vancomycin-resistant enterococci isolated from selected human, poultry and pig populations in Peninsular Malaysia - Molla, Yitbarek Getachew (2010)
Farm animals have been implicated as source and reservoirs of vancomycin-resistant enterococci (VRE) for human colonization. However, the relative importance of the major food animal reservoirs compared to human and environmental reservoirs is difficult to quantify. In Malaysia, VRE have been a great concern to the poultry farmers in general, especially farms that export their animals to the neighbouring country because of the restriction imposed by the importing country due to the potential risk of VRE transmission to their human population. The present study was carried out to investigate the epidemiology of VRE in selected human (poultry workers, veterinary students and pig butchers), poultry and pig populations in Peninsular Malaysia. The specific objectives of the study were to detect and describe VRE, identify the epidemiological risk factors for colonization with VRE, determine the vancomycin-resistance genes and vancomycin-susceptibility pattern, detect virulence and enterocin genes, determine genetic diversity of VRE species, and elucidate the genetic relatedness of E. faecalis and E. faecium isolates from human and animals. VRE were detected in 28 (9.4%) of apparently healthy humans, specifically in four (4.3%) of the veterinary students, 15 (13.5%) of poultry workers and 9 (9.5%) of pig butchers. Risk factor analyses showed that previously hospitalized individuals were 4 times more likely to be VRE positive than non-hospitalized. Older (age ≥ 40 years) individuals were 5 times more likely to be colonized than younger subjects (age < 40 years). VRE were detected in 32 (12%) and 1 (0.4%) of pigs and poultry samples respectively. However, factors contributing for VRE colonization in pigs and poultry were not evident. There was no evidence to suggest that contact with animals significantly contribute to VRE among the examined human population. Enterococcus faecalis, E. faecium, E. gallinarum, E. casseliflavus, E. durans and E. hirae were detected. E. faecium was the dominant species in human, E. faecalis was common in poultry while E. casseliflavus was abundant in pigs. Interestingly, other than VRE, highly vancomycin-resistant Gram-positive cocci (VRC) bacteria were detected. Selected VRC were identified as Pediococcus species. This incidental finding suggested that potentially high numbers of VRE false positive farms have been detected using the conventional VRE identification system. Vancomycin-resistance gene vanB was only detected in one of E. faecalis isolate obtained from human making it the first report in Malaysia. The gene vanA was detected in 20 (71%), 7 (13%) and 51 (36%) humans, pigs and poultry VRE isolates respectively. The prevalence of intrinsic vancomycin resistance genes vanC1 and vanC2/3 was the same as E. gallinarum and E. casseliflavus respectively. However,E. gallinarum isolates that acquired vanA gene were observed. In general vanA carrying VRE isolates were noted to be highly resistant (MIC ≥ 256μg/mL) while majority of vanC isolates were intermediately resistant. Virulence gene gelE was detected in 75 (95%) of E. faecalis and 41(71%) of E. faecium isolates. CylA gene was present in 5 (6%) E. faecalis and 2 (3%) E. faecium isolates. The esp gene was detected in 4 (5%) and 8 (14%) of E. faecalis and E. faecium isolates respectively. Among 79 E. faecalis, 3 (4%) entA, 4 (5%) entB, 6 (7.6%) entP and 19 (24%) ent31 gene harbouring isolates were identified. Likewise, from 58 E. faecium isolates, 31 (53%), 8 (14%), 21 (36%) and 1 (0.6%) of them were positive for entA, entB, ent31 and entL50AB genes, respectively. Meanwhile, enterocin genes were rare in other species. The finding highlighted the presence of trait aiding spread, survival and dominance of VRE in microbial ecology. In this study RAPD was used to determine the genetic diversity of VRE isolates obtained from humans, pigs and poultry. High genetic diversity was generally seen in E. faecalis, E. faecium, E. gallinarum and E. casseliflavus. RAPD was a rapid technique that allowed characterizing a number of isolates at a time. However, RAPD method showed low reproducibility and failed to differentiate strains with vanA genes from those without van genes. Multilocus sequence typing of selected 14 E. faecium and 11 E. faecalis revealed six sequence types (ST) for E. faecium (ST203, ST17, ST55, ST29 and ST79) and E. faecalis (ST4, ST6, ST87, ST108, ST274 and ST244) respectively. Clustering analysis showed that more than 70% of E. faecium and all E. faecalis were hosts specific (human, pig and poultry). E. faecium isolates from healthy individuals had close similarity to clinical isolate (D, 0-14), but there was high dissimilarity (D, 20) between animal and human isolates in general. Most of human E. faecium isolates were derivatives of the epidemic strain clonal complex (CC) -17. Two of human E. faecalis were derived from epidemic CC2 and CC87. Only one poultry E. faecium was part of the epidemic CC17. E. faecium strains reported from Singapore have close similarity to human isolates (D, 7) but high degree of variation (Distance 19 – 29) from animal isolates characterized in this study. Similar E. faecium ST17 stains are reported from 21 countries. Mainly from the Western countries, Australia and Korea. E. faecium ST203 is reported from four Asian and three European countries. Australia, Belgium, France, Brazil and Netherlands were countries that reported ST57 and ST29. Netherland was the only country in MLST database where ST55 was reported. Similar strain of E. faecalis ST4 identified in present study was reported from Thailand. The overall finding from this part of the study is highly significant in the context of refuting the claims that poultry products in Malaysia potentially lead to human VRE colonization in Singapore. The findings from this study have contributed significantly to the understanding on the distribution and types of VRE among healthy humans, pigs and poultry. The study has elucidated the potential risk factors among humans for VRE colonization, types of resistances, virulence and enterocin genes present, genetic characteristics, and has given first insight into MLST profiles and genetic relatedness of human and animal VRE stains circulating in Malaysia. The study has provided evidence that can be used in the future should the issue on human-animal VRE transmission arise in Malaysia.